2012
DOI: 10.1002/ajh.23154
|View full text |Cite
|
Sign up to set email alerts
|

Hyposplenism: Comparison of different methods for determining splenic function

Abstract: Asplenic patients are at risk for pneumococcal sepsis. Patients with hyposplenic function, such as associated with sickle cell disease (SCD), are also at risk. However, tests to assess splenic function are either unavailable or lacking standardization. The aim of this study was to compare different methods for determining splenic function. Eighteen patients with SCD (i.e., 10 heterozygous (SC) and 8 homozygous (SS) SCD patients), and eight splenectomized patients were compared to 10 controls. All subjects unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
80
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 65 publications
(88 citation statements)
references
References 32 publications
(41 reference statements)
3
80
0
5
Order By: Relevance
“…To the editor: We read with great interest the article by Lammers et al [1] reporting on the clinical value of several markers of altered splenic function (hyposplenism). We also recently performed a study to identify relevant markers of hyposplenism.…”
Section: Reduced Deformability Of Circulating Erythrocytes: a Marker mentioning
confidence: 99%
“…To the editor: We read with great interest the article by Lammers et al [1] reporting on the clinical value of several markers of altered splenic function (hyposplenism). We also recently performed a study to identify relevant markers of hyposplenism.…”
Section: Reduced Deformability Of Circulating Erythrocytes: a Marker mentioning
confidence: 99%
“…The SAE patients who were included were compared to previously studied surgically treated patients and to healthy controls (HC) (17). The serum samples of these patients and controls (who received the same vaccines and tests as did the SAE patients) had been stored, and their levels of antibodies against pneumococcal polysaccharides were reanalyzed, since a new method with new reference values had been introduced.…”
Section: Patientsmentioning
confidence: 99%
“…Three types of B cells were specified: naive cells (IgD (17). Lymphocytes were analyzed only once (before vaccination), since previous work has shown that there were no differences in absolute cell counts or in percentages between pre-and postvaccination samples (17). HJB were made visible in the peripheral blood smear of fresh EDTA blood by Pappenheim (basophilic) staining (combination of May-Grunwald and Giemsa).…”
Section: Patientsmentioning
confidence: 99%
See 2 more Smart Citations